2012
DOI: 10.1111/j.1521-0391.2012.00225.x
|View full text |Cite
|
Sign up to set email alerts
|

Decision Making, Impulsivity, and Personality Traits in Alcohol‐Dependent Subjects

Abstract: The aim of the study was to assess the relationship among decision-making (DM) ability (as measured by the Iowa Gambling Task [IGT]), impulsivity, and temperament and character traits in a long-term abstinent alcohol-dependent sample. Twenty-six abstinent alcohol-dependent subjects, referred to a Drug Addiction Unit of the National Health Service of L'Aquila, were evaluated using the IGT, the Barratt Impulsiveness Scale, version 11 (BIS-11), and the Temperament and Character Inventory 125-item (TCI-125) versio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
38
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 41 publications
(47 reference statements)
6
38
0
4
Order By: Relevance
“…Accordingly, a recent meta-analysis indicated that non-planning impulsivity was increased in remitted bipolar patients in comparison to healthy controls (Saddichha and Schuetz, 2014). In addition, non-planning impulsivity has been also correlated with decision making processes, evaluated by the Iowa Gambling Task, in euthymic bipolar patients (Christodoulou et al, 2006) as well as in alcohol-dependent subjects (Tomassini et al, 2012). As a consequence, we hypothesize that higher nonplanning impulsivity may have a strong negative effect on adherence to medication in euthymic bipolar patients.…”
Section: Introductionmentioning
confidence: 85%
“…Accordingly, a recent meta-analysis indicated that non-planning impulsivity was increased in remitted bipolar patients in comparison to healthy controls (Saddichha and Schuetz, 2014). In addition, non-planning impulsivity has been also correlated with decision making processes, evaluated by the Iowa Gambling Task, in euthymic bipolar patients (Christodoulou et al, 2006) as well as in alcohol-dependent subjects (Tomassini et al, 2012). As a consequence, we hypothesize that higher nonplanning impulsivity may have a strong negative effect on adherence to medication in euthymic bipolar patients.…”
Section: Introductionmentioning
confidence: 85%
“…As reported in several studies, alcohol dependence is associated with antisocial behaviour [3,4] as well as with anxiety and mood disturbances [5,6]. This is reflected by high scores on personality scales measuring aggression, impulsivity and sensation seeking, as well as traits related to neuroticism which is marked by stress sensitivity, anxiety and depression [4,5,6,7,8,9,10,11,12,13,14]. Accordingly, it was supposed that persons of the former type tend to drink to enhance their uncontrolled satisfaction of immediate needs and increase their self-esteem, whereas those prone to neurotic traits will use alcohol as a coping strategy to forget about problems and to alleviate worries [11,13,15,16].…”
Section: Introductionmentioning
confidence: 96%
“…Both types of impulsivity, as well as suboptimal decision making, have been associated with the susceptibility for AUD (Bates and Labouvie 1997; Dom et al 2006; Ernst et al 2006; Verdejo-Garcia et al 2008; de Wit 2009; Fernie et al 2010; Goudriaan et al 2011; King et al 2011; Fernie et al 2013). Conversely, excessive alcohol use has also been shown to result in exaggerated impulsivity and suboptimal decision making (Vuchinich and Simpson 1998; Petry 2001; Field et al 2007; Perry and Carroll 2008; Salgado et al 2009; Kim et al 2011; MacKillop et al 2011; Tomassini et al 2012; Voon et al 2013). Together, these findings suggest a complex bidirectionality between impaired impulse control and decision making on the one hand and AUD on the other.…”
Section: Introductionmentioning
confidence: 99%